Kurt Stern : journal du 1er septembre 1939 au 19 décembre 1939 / Guylain CHEVRIER, Gilbert BADIA, Kurt STERN - BADIA, Gilbert; CHEVRIER, Guylain; STERN, Kurt
L'article fait partie de la rubrique : Métiers. Au sources de l'histoire. //